2019
DOI: 10.1007/s00167-019-05504-4
|View full text |Cite
|
Sign up to set email alerts
|

Meniscal allograft transplantation after meniscectomy: clinical effectiveness and cost-effectiveness

Abstract: Purpose To assess the clinical effectiveness and cost-effectiveness of meniscal allograft transplantation (MAT) after meniscal injury and subsequent meniscectomy. Methods Systematic review of clinical effectiveness and cost-effectiveness analysis. Results There is considerable evidence from observational studies, of improvement in symptoms after meniscal allograft transplantation, but we found only one small pilot trial with a randomised comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 58 publications
(241 reference statements)
1
38
0
Order By: Relevance
“…Once the patient becomes meniscus-deficient, the outcomes after meniscal transplantation are worse than if the patient underwent meniscal repair at their index procedure. 39 The increased rate of knee arthroplasty after meniscectomy further confirms the results of previous studies, with up to 51.5% of patients requiring knee arthroplasty after meniscectomy compared with 33.5% after meniscal repair at the 10-year follow-up. 1,5,13,29 Abram et al 1 utilized the National Health Service database of England to determine that 0.67% of patients who underwent meniscectomy between the ages of 20 and 39 years required subsequent knee arthroplasty.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Once the patient becomes meniscus-deficient, the outcomes after meniscal transplantation are worse than if the patient underwent meniscal repair at their index procedure. 39 The increased rate of knee arthroplasty after meniscectomy further confirms the results of previous studies, with up to 51.5% of patients requiring knee arthroplasty after meniscectomy compared with 33.5% after meniscal repair at the 10-year follow-up. 1,5,13,29 Abram et al 1 utilized the National Health Service database of England to determine that 0.67% of patients who underwent meniscectomy between the ages of 20 and 39 years required subsequent knee arthroplasty.…”
Section: Discussionsupporting
confidence: 87%
“…Once the patient becomes meniscus-deficient, the outcomes after meniscal transplantation are worse than if the patient underwent meniscal repair at their index procedure. 39…”
Section: Discussionmentioning
confidence: 99%
“…One study found no clear evidence of cost-effectiveness for either APM or meniscal scaffold procedures, whereas the other study found that APM was more cost-effective than MAT in the short term but MAT was more effective at delaying total knee arthroplasty in the long term compared with APM. Waugh et al 139 set out to examine cost-effectiveness of MAT in a systematic review; however, they found that a cost-effectiveness analysis was not feasible because they did not find any studies that compared MAT versus nonoperative management.…”
Section: Resultsmentioning
confidence: 99%
“…Two systematic reviews demonstrated good clinical outcomes after MAT, although both concluded that there was insufficient evidence for determining the chondroprotective effects of MAT. 113,139 In a systematic review and meta-analysis of 17 animal studies, MAT was associated with less gross macroscopic cartilage damage compared with meniscectomy but more damage compared with a control group. 112 No difference in osteoarthritic changes after MAT versus meniscectomy was seen, although MAT was associated with more osteoarthritic changes versus a control group.…”
Section: Meniscal Allograft Transplantationmentioning
confidence: 99%
“…Surgical techniques for implantation include soft‐tissue, bone plug, and bone bridge methods for root fixation, followed by menisco‐capsular suture repair 9,16 . While these grafts and techniques have proven safe and effective in general, complications including shrinkage, extrusion, progression of joint pathology, and failure persist 9,16,17 that negatively influence outcomes, patient satisfaction, and long‐term survivorship due to revision and removal (6%‐27%) or conversion to total knee arthroplasty (19%) 10,18‐21 …”
Section: Introductionmentioning
confidence: 99%